Bahasa Inggris - Dewi Sulistyowati; Hernani Hernani; Asep Supriatna; Anita Fadhilah; Aldini Aulia (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to develop teaching-learning sequences (TLS) in the context of edible coatings for fruits and vegetables that integrate Education for Sustainable Development (ESD) in economic, environmental, and social aspects. TLS can be applied to create lesson plans or teaching materials in chemistry learning. This research used Qualitative Content Analysis, following four key stages: material collection, descriptive analysis, category selection, and material evaluation. Data were gathered from the analysis of fifty-eight literature sources and validated by five experts in terms of content validity. Validation experts are experienced four lecturers from chemistry education field and one doctoral student. The results of this research are as follows: TLS divided into four sections, postharvest losses, edible coating materials, preparation and characterization of edible coatings, and potential edible coatings to support sustainable living based on SDG-related points Zero Hunger (SDG 2), Good Health and Well-Being (SDG 3), Quality Education (SDG 4), Industry, Innovation, and Infrastructure (SDG 9), Responsible Consumption and Production (SDG 12), Climate Action (SDG 13), and Life on Land (SDG 15). The validation confirmed that the TLS content is appropriate for chemistry learning with ESD content